Development and poverty in sub-Saharan Africa - Tony Addison; Ville Pikkarainen; Risto Rönkkö; Finn Tarp (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
This paper puts sub-Saharan Africa's economic development into perspective. While much did not go as hoped for at independence, much of the region has been on a more promising development trajectory since the mid-1990s, as we illustrate using growth, poverty, and human development indicators. We identify key weaknesses, including lack of structural transformation and the slow rate of employment growth. We refer to global shocks that have played a critical role in sub-Saharan Africa's economic performance alongside domestic events, policies, and governance. Finally, we discuss a set of critical challenges requiring effective management for sub-Saharan Africa to realize its considerable development potential.
Keywords: O1; O2; O55; N00; 330; sub-Saharan Africa; economic development; transformation; inclusion; sustainability